Defending Rivers: Vilcabamba in the South of Ecuador - Berros, María Valeria (2017)
Is it possible to give "a legal voice" to a river? For several decades, different disciplines have been debating this possibility within a larger context: could Nature have rights? This article aims at presents the current discussion about Rights of nature recognition as well as to present the recent development on that topic in the Ecuadorian jurisprudence.